4 - Rural-Urban Disparities in Health and Health Care in Africa: Cultural Competence, Lay-beliefs in Narratives of Diabetes among the Rural Poor in the Eastern Cape Province of South Africa - Olajide Oloyede (African Sociological Review, 2017)
Rural-urban disparities in health and health care in Africa have been well described; yet, they remain relatively of less concern among many issues in health and health care in Africa. The disparities have been documented to exist in the utilization of cardiac diagnostic and therapeutic procedures, prescription of analgesia for pains, treatment of diabetes (e.g. gym exercise). Among the fundamental root causes of these disparities, which, can be gathered through studies of the health care systems (biomedical and African health systems) are variations in patients’ health beliefs, values, preferences and behaviour. Informed by the need to address the seemingly wide rural-urban disparities in health and health care in Africa, this paper brings to the fore rural patients’ recognition of symptoms, threshold for seeking care and the ability to understand disease management strategy, all of which are part of the variations in patients’ health beliefs and values. The strategy adopted for foregrounding these disparities is through narratives of diabetes by patients in a rural context in South Africa. The chief aim is to contribute towards improving the quality of health care through incorporating patients’ understanding of health. The narrative is subsumed under cultural competence and lay beliefs.